Conducting undergraduate research in education : a guide for students in teacher education programs - Palmer, Ruth J.; Thompson, Deborah L. (New York : Routledge, 2022)
This book offers a student-focused guide to conducting undergraduate research in education and education-related programs, engaging students in the process of learning through research and supporting them to navigate their multidimensional academic programs. Written for undergraduate students in teacher education programs, the book features a range of leading voices in the field who offer a step-by-step guide to all elements of the research process: from conducting a literature review and choosing a research topic, to collecting data and building a research community with peers and mentors. Ultimately, volume editors Ruth J. Palmer and Deborah L. Thompson help model the competencies that students need to succeed, including complex thinking, strategic design, modeling, and persistent iterative practice, while demonstrating how conducting research can help students develop as deep thinkers, courageous researchers, and active participants in their communities of practice. Offering strategic approaches, support, and guidance, this book demonstrates the wider importance of undergraduate research in informing educational practice and policy, as well as understanding schools beyond the classroom context, encouraging active engagement and continued learning progression.
1: Undergraduate Research in Teacher Education: The Legacy, the Promise, the Responsibility by Ruth J. Thompson 2: Beginning the Investigation: The Research Question by Sylvia Talia 3: Building a Foundation for Undergraduate Research in Teacher Education: The Literature Review by Suzanne Lindt and Emily Smith4: The Demands of Reading, Writing, and Thinking like Researchers by Deborah L. Thompson5: Technology: The All-Purpose Research Tool for Discovery, Organization, andCollaboration by Judi Puritz Cook6: Building Essential Components of a Research Project: Determining Topic, Research Design, and Ethical Conduct need by Giang-Nguyen T. Nguyen and Carla J. Thompson7: Data Analysis: The Heart of the Research Study by Deborah L. Thompson8: Building a Research Community with Peers, Near-Peers, and Experienced Mentors by Catherine L. Packer-Williams 9: Report Writing for Undergraduate Research in Teacher Education: Findings and Discussion by Arti Joshi and Jody Eberly10: Report Writing II: Dissemination and Emerging Innovative Approaches by Jody Eberly and Arti Joshi11: Toward Excellence in Undergraduate Research in Teacher Education Programs: Practice, Persistence, and Partnerships by Ruth J. Palmer
Keywords: Education -- Research -- Methodology; EDUCATION / Research